Designing and manufacturing of a lightweight and broadband electromagnetic wave absorber with combined carbonaceous and magnetic nanofillers. Issue 4 (May 2019) - Haq, Izhar ul; Khurram, AA; Hussain, Rizwan; Naseem, Shahzad
Two different types of microwave absorbers composed of two layers and four layers of nanocomposites have been designed in the light of the theory of electromagnetic wave absorbers and tested. The nanocomposites were prepared from glass fiber/epoxy filled with carbonaceous and magnetic nanoparticles. The carbonaceous nanoparticles include multiwalled carbon nanotubes, graphene nanoplatelets (GNPs), and thermally exfoliated GNPs, whereas magnetic nanoparticles include CoFe3 O4, CoNiFe3 O4, MnFe3 O4 in different weight percentage. The absorbers with two layers of nanocomposites had total designed thickness of 3.3 mm. The surface layer of those absorbers is made of lower permittivity nanocomposite as compared to the bottom layer. On the other hand, the absorbers with four layers of nanocomposites have alternating combination of layers filled with carbonaceous and magnetic nanoparticles. The measurement of reflectivity using free space method have shown that among all the designed microwave absorbers, one of the absorber with two layers of nanocomposites have shown least reflectivity (−24 dB) and higher −10 dB bandwidth (9 GHz). That absorber is composed of low permittivity surface layer filled with equal wt% (4 wt%) of magnetic nanoparticles, that is, CoFe3 O4, CoNiFe3 O4, MnFe3 O4, and a bottom lossy layer filled with 2.6 wt% of carbon nanotubes.